Kemampuan Metabolit Sekunder Bakteri Laut Menghambat Pertumbuhan Vibrio parachaemolyticus dan Stophylococcus aureus - Widiastuti H.N. (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
This study is to find out the ability of the secondary metabolites of the marine bacteries to inhibit Vibrio parahaemolyticus and Staphylococcus aureus. Water samples were taken from Jepara Coast. The samples were analyzed for the presence of Marinebacterias by isolation and identification. Sensitivity of the marine bacterias to inhibit the growth of Vibrio parahaemolyticus and Staphylococcus aureus as characterized by incubation for 24, 48, and 72 hr at the paper disks surronded by media inoculated with Vibrio parahaemolyticus and Staphylococcus aureus. Sensitivity was indicated by the diameter of inhibition zone formed during incubation. Results indicated that the coastal water contained Pesudomonas spp, Bacillus spp., Flavobacterium sp. and Nocardia sp. which produced secondary metabolites that inhibited the growth of Vibrio parahaemolyticus and Staphylococcus aureus in 48 hours incubation.